A Personal Account on Inorganic Reaction Mechanisms - Polaczek, Justyna; Kieca, Konrad; Oszajca, Maria; Impert, Olga; Katafias, Anna; Chatterjee, Debabrata; Ćoćić, Dušan; Puchta, Ralph; Stochel, Grażyna; Hubbard, Colin D.; van Eldik, Rudi (Chemical Record, 2023)
The presented Review is focused on the latest research in the field of inorganic chemistry performed by the van Eldik group and his collaborators. The first part of the manuscript concentrates on the interaction of nitric oxide and its derivatives with biologically important compounds. We summarized mechanistic information on the interaction between model porphyrin systems (microperoxidase) and NO as well as the recent studies on the formation of nitrosylcobalamin (CblNO). The following sections cover the characterization of the Ru(II)/Ru(III) mixed-valence ion-pair complexes, including Ru(II)/Ru(III)(edta) complexes. The last part concerns the latest mechanistic information on the DFT techniques applications. Each section presents the most important results with the mechanistic interpretations.
CRIS-Team Scopus Importer:2023-10-20